Using acoustic emission and fractography to evaluate defects induced by corrosive environment - Hrairi, Meftah (Maney Publishing, 2009)
Acoustic emission (AE) is now a well established technique for damage detection, quantification and location in large structures. It appears in its principle as a technique providing real time information about the origins and the importance of the degradation mechanisms inside the material. This paper demonstrates the use of AE technique to monitor the structural damage using data obtained from a phenomenological study of hydrogen induced cracking of a low alloy steel pressure vessel. In addition to the feature extraction, correlation and clustering procedures applied to the AE signals, data were studied in time and frequency domain to characterise and to find out the relation between AE parameter and damage sources. Moreover, the characterisation of the corrosive mechanisms using the optical microscopy as well as the scanning electron microscopy was carried out. These identified corrosive mechanisms and the sources of generated AE signals were discussed.